Blow-up of solutions for the damped Boussinesq equation - Polat, N; Kaya, D; Tutalar, HI (Walter de Gruyter Gmbh, 2005)
We consider the blow-up of solutions as a function of time to the initial boundary value problem for the damped Boussinesq equation. Under some assumptions we prove that the solutions with vanishing initial energy blow up in finite time.
Keywords: damped Boussinesq equation; blow-up of solutions; initial boundary value problems; Sobolev-Poincare inequality; Holder inequality